2019
DOI: 10.1111/jcpe.13196
|View full text |Cite
|
Sign up to set email alerts
|

Gingiva thickening with a porcine collagen matrix in a preclinical dog model: Histological outcomes

Abstract: Aim To compare 10‐month histological and immunohistological outcomes after soft tissue thickening around teeth with a porcine collagen matrix (CM) versus a subepithelial connective tissue graft (SCTG). Material and Methods In eight beagle dogs, soft tissue thickening of the buccal gingiva of upper canines was performed with the SCTG or the CM. Connective tissue thickness (CTT) was histomorphometrically measured in the augmented regions. The augmented connective tissues were also histologically characterized an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…Hence, 100% of the articles analysed in this study support the statement that Col can be used for gingival healing [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, 13% of the researchers emphasise that Col has less potential for GR healing compared with SCTG [ 14 , 18 ]. Two studies in this review analysed the physicochemical properties of the Col-based scaffold and the effect of the scaffold in GR [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Hence, 100% of the articles analysed in this study support the statement that Col can be used for gingival healing [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, 13% of the researchers emphasise that Col has less potential for GR healing compared with SCTG [ 14 , 18 ]. Two studies in this review analysed the physicochemical properties of the Col-based scaffold and the effect of the scaffold in GR [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 71%
“…In contrast, direct bonding of CT to the periosteum and with a matured Col fibre was observed in both groups. There was no significant difference seen for a vascular endothelial growth factor (VEGF) and Col-I expression in both groups [ 14 ]. These findings showed that SCTG outranges Col matrix as the current approved gold standard treatment for GR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratinized tissue gain was attributed to the natural tendency of the mucogingival junction to regain its original, genetically determined position . The change can also be related with xenogeneic CTG substitutes, which replaced the host tissues with the desired histologic and functional characteristics and lead to augmentation in both the width and the thickness of keratinized band …”
Section: Discussionmentioning
confidence: 99%